Reducing antibiotic prescribing for children with respiratory tract infections in primary care: a systematic review. - Vodicka, T; Thompson, M; Lucas, P; Heneghan, C; Blair, P; Buckley, D; Redmond, N; Hay, A (2013)
BACKGROUND: Respiratory tract infections (RTIs) in children are common and often result in antibiotic prescription despite their typically self-limiting course. AIM: To assess the effectiveness of primary care based interventions to reduce antibiotic prescribing for children with RTIs. DESIGN AND SETTING: Systematic review. METHOD: MEDLINE(®), Embase, CINAHL(®), PsycINFO, and the Cochrane library were searched for randomised, cluster randomised, and non-randomised studies testing educational and/or behavioural interventions to change antibiotic prescribing for children (<18 years) with RTIs. Main outcomes included change in proportion of total antibiotic prescribing or change in 'appropriate' prescribing for RTIs. Narrative analysis of included studies was used to identify components of effective interventions. RESULTS: Of 6301 references identified through database searching, 17 studies were included. Interventions that combined parent education with clinician behaviour change decreased antibiotic prescribing rates by between 6-21%; structuring the parent-clinician interaction during the consultation may further increase the effectiveness of these interventions. Automatic computerised prescribing prompts increased prescribing appropriateness, while passive information, in the form of waiting room educational materials, yielded no benefit. CONCLUSION: Conflicting evidence from the included studies found that interventions directed towards parents and/or clinicians can reduce rates of antibiotic prescribing. The most effective interventions target both parents and clinicians during consultations, provide automatic prescribing prompts, and promote clinician leadership in the intervention design.